Byzantine Consensus with Secure and Intrusion-Tolerant In-Network Ordering - Rocha, Gabriel Faustino Lima da; Alchieri, Eduardo A. P.; Venâncio, Giovanni; Fulber-Garcia, Vinicius; Duarte Jr., Elias P. (Anais do Latin-American Symposium on Dependable Computing (LADC); 2025: Anais do XIV Latin-American Symposium on Dependable Computing, 2025)
Recently proposed consensus protocols make use of the network layer to ensure agreement, while the application layer is still used for termination. Those protocols employ the network layer as a sequencer that delivers ordered messages facilitating agreement. However, tolerating a malicious sequencer is a challenging task. For instance, a malicious sequencer can assign the same sequence number to different messages and send them to different replicas. To avoid this problem, the NeoBFT consensus protocol adds an additional communication step at the replicas. Although this approach mitigates the problem, it negatively impacts system performance by requiring an additional synchronization step among replicas before executing requests. This work proposes NsoBFT (Network Secure Ordered BFT), a consensus protocol that uses a secure message ordering service implemented with USIG (Unique Sequential Identifier Generator), a secure component in the network layer. Thus, no additional synchronization step is necessary for the replicas to execute requests. Experimental results comparing NsoBFT with related work show the advantage of this strategy, in particular confirming that NsoBFT outperforms NeoBFT.